2013
DOI: 10.5009/gnl.2013.7.6.629
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the α 2, 6 Sialylation of Glycoproteins May Contribute to Metastatic Spread and Therapeutic Resistance in Colorectal Cancer

Abstract: Abnormal glycosylation due to dysregulated glycosyltransferases and glycosidases is a key phenomenon of many malignancies, including colorectal cancer (CRC). In particular, increased ST6 Gal I (β-galactoside α 2, 6 sialyltransferase) and subsequently elevated levels of cell-surface α 2, 6-linked sialic acids have been associated with metastasis and therapeutic failure in CRC. As many CRC patients experience metastasis to the liver or lung and fail to respond to curative therapies, intensive research efforts ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 156 publications
5
70
3
Order By: Relevance
“…71 For example, abnormal glycosylation of some glycoproteins due to deregulated glycosyltransferases and glycosidases is known to be a common phenomenon of many malignancies, including colorectal cancer (CRC), where elevated levels of the cell-surface α 2,6-linked sialic acids have been linked to metastatic spread and therapeutic resistance of this cancer. 72 The widespread and diverse PTMs of histones, important nuclear IDPs 73 that are crucial for regulated gene expression and for a variety of epigenetic mechanisms, are under very tight and complex spatial and temporal control. 74 This spatial and temporal regulation of histone modifications is distorted in malignancies on both genome-wide and discrete gene loci levels.…”
Section: Regulation Of Intrinsically Disordered Proteins and Diseasementioning
confidence: 99%
“…71 For example, abnormal glycosylation of some glycoproteins due to deregulated glycosyltransferases and glycosidases is known to be a common phenomenon of many malignancies, including colorectal cancer (CRC), where elevated levels of the cell-surface α 2,6-linked sialic acids have been linked to metastatic spread and therapeutic resistance of this cancer. 72 The widespread and diverse PTMs of histones, important nuclear IDPs 73 that are crucial for regulated gene expression and for a variety of epigenetic mechanisms, are under very tight and complex spatial and temporal control. 74 This spatial and temporal regulation of histone modifications is distorted in malignancies on both genome-wide and discrete gene loci levels.…”
Section: Regulation Of Intrinsically Disordered Proteins and Diseasementioning
confidence: 99%
“…These structures may be directly associated with β1-6 branching of Asn-linked oligosaccharides [91]. A detailed review by Park and Lee [104] summarizes how β-galactoside α2,6 sialyltransferase (ST6 Gal I) with subsequent elevated levels of cell-surface α2,6 -linked sialic acids have been implicated in the altered expression of sialylated glycoproteins with their linkage to colorectal cancer metastasis, radio-resistance, and chemoresistance.…”
Section: Aberrant Sialylation In Cancer Progression and Metastasismentioning
confidence: 99%
“…They found that Ssa-I decreased the migratory ability of cells and concomitantly enhanced cell adhesion to extracellular matrix proteins. Furthermore, Park and Lee [104] found that increasing STGal-I (β-galactoside α2,6 sialyltransferase) elevated the levels of cell-surface α2,6-linked sialic acids on proteins which have been associated with metastatic spread and therapeutic resistance in colorectal cancer. Collectively, sialyltransferases are mainly expressed in the Golgi apparatus where they incorporate sialic acid residues into assembling glycan structures of cell surface glycoproteins and lipids.…”
Section: Aberrant Sialylation In Cancer Progression and Metastasismentioning
confidence: 99%
“…The majority of mortalities caused by colorectal cancer are due to metastatic disease (4). As numerous CRC patients experience metastasis to the liver or lung and fail to respond to curative therapies, significant research efforts have aimed to identify the molecular changes or regulatory mechanisms underlying CRC metastasis (5). The present study, focusing on the differences of miRNA expression in HCT16 cell lines located in the lung and colon aimed to examine the potential miRNA targets associated with the regulation of colorectal lung metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic spread to the liver and lungs occurs most frequently in colorectal cancer metastases in humans (4). Numerous CRC patients experience metastasis to the liver or lung and fail to respond to curative therapies, thus significant research efforts have focused on identifying the molecular changes underlying CRC metastasis (5). Several candidate biomarkers have been reported, including ST6 galactose I and β1 integrin (6,7).…”
Section: Introductionmentioning
confidence: 98%